The best interest of the student: an approach to its content, evaluation and Determination - Michael Espinoza Coila (2014)
This article presents a brief investigation that had the following objectives: to define the best interest of the student, establish its objective, indicate its dimensions, explain the relationship it has with education, and explain how to evaluate and determine the best interest of the student. ; By means of the legal method, the best interest of the student is defined, as the one whose primary consideration is to attend to the interest of the student in all the measures concerning the students taken by the universities, with the aim of guaranteeing the full and effective enjoyment of the right. to education, it is manifested in three dimensions: as a substantive right, an interpretative legal principle and a procedural rule; and being a parabolic concept, it maintains a connection with the fundamental rights recognized in the Constitution and the International Law of Human Rights and the principles of the University Law; For its concrete application, the evaluation and determination of its content is required, which consists of evaluating and weighing all the elements or circumstances necessary to make a decision in a given situation for the students, and developing structured processes with rules and guarantees.